Combined methods at low temperature to minimize quality loss in acerola and jaboticaba: immersion in CaCl2, freezing, and freeze-drying - BORGES, Rhinery Beatriz Rocha; MEIRA, Ana Cristina Freitas de Oliveira; DAMIANI, Clarissa; RESENDE, Jaime Vilela de (Food Science and Technology, 2023)
The objective of this study was to investigate the effects of combined processes at low temperature on the quality of acerola (Malpighia punicifolia L.) and jaboticaba (Myrciaria cauliflora Berg). Acerola and jaboticaba were subjected to different combined treatments: infusion in calcium chloride, freezing at different temperatures (-20 and -80 °C) and freeze-drying. Physicochemical, colorimetric, scanning electron microscopy (SEM), and texture (firmness) analyses were conducted for acerola and jaboticaba fruits, and rheological behavior was analyzed in jaboticaba pulp. According to the results, for acerola, infusion in CaCl2 interfered with microstructural analysis, freezing at -20 °C damaged the fruit, and freeze-drying with freezing at -80 °C yielded fruits with the most satisfactory quality. For jaboticaba, CaCl2 infusion significantly changed the microstructure and pulp viscosity, and freezing at -20 °C further damaged the fruit; the best colorimetric results were obtained for freeze-drying with freezing at -80 °C.